Personalized cancer chemotherapy an effective way of enhancing outcomes in clinics - Lu, Da-Yong 1962- (Woodhead Publishing series in biomedicine, 2015)
Individualized cancer chemotherapy (ICC) has been designed to meet the requirement of selecting anticancer drugs in clinics and attracting increasing attentions in medical circle and will show more beneficial outcome in the future if we stick on these researches. Personalized Cancer Chemotherapy addresses and reviews this issue by discussing many existing specific strategies of ICC, including drug sensitivity testing, cancer biomarker detections, cancer biomarker-oriented therapy, anticancer drug pharmacogenetics, cancer metastasis therapy, anticancer drug combinations, assistant therapy, mathematics, and computational analysis of cancer malignancy and drug responses, cost effective and finally studies of relationship between different ICC strategies. The relationship between drug response and these techniques or methods is in-depth analyzed, discussed and highlight. Many longstanding key debates and future trends are also intensively discussed, highlighted and debuted with new twists